Endothelial SMAD1/5 signaling couples angiogenesis to osteogenesis in juvenile bone - Annemarie Lang; Andreas Benn; Joseph M. Collins; Angelique Wolter; Tim Balcaen; Greet Kerckhofs; An Zwijsen; Joel D. Boerckel (Communications Biology, 2024)
Abstract Skeletal development depends on coordinated angiogenesis and osteogenesis. Bone morphogenetic proteins direct bone formation in part by activating SMAD1/5 signaling in osteoblasts. However, the role of SMAD1/5 in skeletal endothelium is unknown. Here, we found that endothelial cell-conditional SMAD1/5 depletion in juvenile mice caused metaphyseal and diaphyseal hypervascularity, resulting in altered trabecular and cortical bone formation. SMAD1/5 depletion induced excessive sprouting and disrupting the morphology of the metaphyseal vessels, with impaired anastomotic loop formation at the chondro-osseous junction. Endothelial SMAD1/5 depletion impaired growth plate resorption and, upon long-term depletion, abrogated osteoprogenitor recruitment to the primary spongiosa. Finally, in the diaphysis, endothelial SMAD1/5 activity was necessary to maintain the sinusoidal phenotype, with SMAD1/5 depletion inducing formation of large vascular loops and elevated vascular permeability. Together, endothelial SMAD1/5 activity sustains skeletal vascular morphogenesis and function and coordinates growth plate remodeling and osteoprogenitor recruitment dynamics in juvenile mouse bone.